Estimation of optimum specific light intensity per cell on a high-cell-density continuous culture of Chlorella zofingiensis not limited by nutrients or CO2 - Imaizumi, Yuki; Nagao, Norio; Md. Yusoff, Fatimah; Taguchi, Satoru; Toda, Tatsuki (Elsevier, 2014)
To determine the optimum light intensity per cell required for rapid growth regardless of cell density, continuous cultures of the microalga Chlorella zofingiensis were grown with a sufficient supply of nutrients and CO2 and were subjected to different light intensities in the range of 75–1000 μE m−2 s−1. The cell density of culture increased over time for all light conditions except for the early stage of the high light condition of 1000 μE m−2 s−1. The light intensity per cell required for the high specific growth rate of 0.5 day−1 was determined to be 28–45 μE g-ds−1 s−1. The specific growth rate was significantly correlated to light intensity (y = 0.721 × x/(66.98 + x), r2 = 0.85, p < 0.05). A high specific growth rate was maintained over a range of light intensities (250–1000 μE m−2 s−1). This range of light intensities suggested that effective production of C. zofingiensis can be maintained outdoors under strong light by using the optimum specific light intensity.